GAMBARAN FAKTOR-FAKTOR YANG MENDORONG KEPUTUSAN KELUARGA DALAM MEMANFAATKAN PELAYANAN RAWAT INAP DI PUSKESMAS NGEMPLAK I SLEMAN - Widayati, Nur; Dewi, Erti Ikhtiarini (FKM - UNEJ, 2007)
Public Health Center of Ngemplak I is one of Public Health Center at Sleman regency which has hospitalization facilities. Based on Bed Occupancy Rate (BOR) at Public Health Center of Ngemplak I, hospitalization has been utilized optimally. BOR for 2001 was 89,11% and 2002 was 93,8%. Compared with another Public Health Center which has hospitalization facilities at Sleman regency, the utilization of hospitalization facilities at Public Health Center of Ngemplak I is the highest from the other. More over, some people of Prambanan and Kalasan district choose to utilize hospitalization facilities at Public Health Center of Ngemplak I although there is Public Health Center with hospitalization facilities in their district. Â The objective ofÂ this research was to know the description of factors that encourage familyâsÂ decision in utilizing hospitalization facilities at Public Health Center of Ngemplak I Sleman. The method of this research was qualitative. The subject of research was family of patient who hospitalized at Public Health Center of Ngemplak I. Sample was defined by using accidental sampling and consist of 30 people. The instruments of this research were questionnaire and guide interview. The result showed Public Health Center of Ngemplak I was used for hospitalized by family with middle to lower socio economic characteristic with average income Rp.200.000,00-Rp.500.000,00, most of responden work as farmer, labour, lower employee; low to middle education; lived in Ngemplak district, distance from home to Community Health Center < 5 km; and paid the treatment cost by themselves. The factors from service provider that encourage familyâs decision to utilize hospitalization at Public Health Center of Ngemplak I were cheap, near, quickly treatment, friendly Â service, easy administration, good facilities, and complete diagnostic tools. The internal factors that encourage family decision were income, health insurance participation, disease severity, and experience of utilitation Â before. Keywords : familyâs decision, utilization of hospitalization facilities